2019
DOI: 10.1111/resp.13662
|View full text |Cite
|
Sign up to set email alerts
|

Underuse of beta‐blockers by patients with COPD and co‐morbid acute coronary syndrome: A nationwide follow‐up study in New Zealand

Abstract: Background and objective Clinical guidelines recommend the use of beta‐blockers and other cardiovascular prevention drugs in patients with acute coronary syndrome (ACS). Studies in several countries have found that beta‐blockers are underused in patients with chronic obstructive pulmonary disease (COPD) and co‐morbid heart disease, although most have only examined use in subgroups of patients. We undertook a nationwide follow‐up study in New Zealand to describe the use of beta‐blockers and other cardiovascular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…Addressing cardiac comorbidity in COPD is of key interest but the role of beta‐blockers in COPD remains controversial. A nationwide study from New Zealand found only 56.6% of patients with COPD were prescribed beta‐blockers following an acute coronary syndrome 49 . This is despite a meta‐analysis of 49 studies (670 594 patients) observing reduced all‐cause mortality among COPD patients with cardiovascular disease receiving beta‐blockers (HR = 0.69 (0.58–081)) 50 .…”
Section: New Developments In Copdmentioning
confidence: 99%
“…Addressing cardiac comorbidity in COPD is of key interest but the role of beta‐blockers in COPD remains controversial. A nationwide study from New Zealand found only 56.6% of patients with COPD were prescribed beta‐blockers following an acute coronary syndrome 49 . This is despite a meta‐analysis of 49 studies (670 594 patients) observing reduced all‐cause mortality among COPD patients with cardiovascular disease receiving beta‐blockers (HR = 0.69 (0.58–081)) 50 .…”
Section: New Developments In Copdmentioning
confidence: 99%
“… 3 In a study performed in New Zealand of 2637 patients with COPD and indication for β-blockers for acute coronary syndrome, only 57% of patients received such treatment. 18 …”
Section: Underuse Of β-Blockers In Copd Patientsmentioning
confidence: 99%
“…Cardioselective beta-blockers are one of the pillars of treatment for these cardiovascular diseases in the general population. However, beta-blockers are chronically underutilised for these indications in patients with COPD 3 4. This is driven by clinical concern over worsening airflow obstruction, resulting in increased breathlessness and reduced exercise capacity.…”
Section: Introductionmentioning
confidence: 99%